Job satisfaction of community nurses during the Covid-19 pandemic: A qualitative interview study - Kalinowska, Paulina; Marcinowicz, Ludmiła; Dobrzycka, Bożena; Terlikowski, Slawomir (Nursing in the 21st Century, 2023)
JOB SATISFACTION OF COMMUNITY NURSES DURING THE COVID-19 PANDEMIC: A QUALITATIVE INTERVIEW STUDYAim. This study aimed to investigate the job satisfaction of community nurses in the context of the Covid-19 pandemic.Material and methods. A qualitative descriptive study with thematic analysis was conducted. The study involved individual interviews conducted with 20 professionally active community nurses in Poland. The qualitative interviews were conducted via phone from November 2020 to May 2021.Results. Three primary themes were identified in the study: (1) Reasons for job satisfaction; (2) Difficult situations occurring at the workplace; (3) Areas of change that could increase job satisfaction.Conclusions. Greater professional autonomy, sufficient nursing staff, and a clear division of tasks among the members of the health care team seem to be especially important for raising the level of job satisfaction of community nurses.